2023
DOI: 10.3390/molecules28145538
|View full text |Cite
|
Sign up to set email alerts
|

Study on Process Optimization and Antioxidant Activity of Polysaccharide from Bletilla striata Extracted via Deep Eutectic Solvents

Abstract: Taking the extraction yield of Bletilla striata polysaccharide (BSP) as the index and taking the type of deep eutectic solvents (DESs), extraction time, extraction temperature, DES water content, and solid–liquid ratio as the investigation factors, single-factor and Box–Behnken response surface tests were carried out to optimize the extraction process of BSP. Thus, the antioxidant activity of BSP on DPPH radicals, ABTS radicals and ferric reducing antioxidant power were determined. The results showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, it is important to recognize that the co-extraction of phenolic compounds may also have an impact on the antioxidant activity. DESs have been shown to be efficient at extracting nonprotein components with potential for bioactivity, such as polysaccharides and polyphenols (Luo et al, 2023;Redha, 2021).…”
Section: Nutraceutical Potential Of Des-extracted Protein Concentrate...mentioning
confidence: 99%
“…However, it is important to recognize that the co-extraction of phenolic compounds may also have an impact on the antioxidant activity. DESs have been shown to be efficient at extracting nonprotein components with potential for bioactivity, such as polysaccharides and polyphenols (Luo et al, 2023;Redha, 2021).…”
Section: Nutraceutical Potential Of Des-extracted Protein Concentrate...mentioning
confidence: 99%
“…The B. striata plant is mainly distributed in the humid river valleys and coastlands in the most southeastern three provinces of China. Outside China, its global distribution is limited, only growing in the Korean Peninsula, Japan and Myanmar [ 8 ]. Traditionally, it has been used for hemostasis therapy, as well as to treat sores, swelling and chapped skin [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, some regions of China still retain this ancient method of skincare [ 10 ]. The main chemical components of B. striata consist of a variety of chemical substances, such as polysaccharides, benzenes, dihydrophenanthrolines and phenanthrenes, flavonoids, diphenylenes and diphenylene ethers and quinones [ 8 , 11 ]. Therefore, B. striata has a wide range of bio-pharmacological activities, such as bacteriostasis, anti-inflammatory [ 12 ], hemostasis [ 13 ], anti-tumor [ 14 ], cell-growth-promoting and wound healing properties [ 11 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the internal structure of DESs can form hydrogen bonds with target polysaccharides and create electrostatic interactions, significantly improving the extraction efficiency of polysaccharides [ 20 ]. More and more studies have shown that the extraction with DESs of plant active components can not only significantly improve the extraction yield, but also retain the functional activity of the active substances [ 21 , 22 ]. DESs are characterized by their low surface tension and viscosity, which enable them to penetrate into polysaccharides more effectively and enhance extraction efficiency.…”
Section: Introductionmentioning
confidence: 99%